PENGARUH PERLAKUAN AWAL BASA DAN ASAM TERHADAP KADAR GULA REDUKSI TANDAN KOSONGKELAPA SAWIT [The effect of alkali and acid pretreatment on reduced sugar of empty palm fruit bunches] - Sutikno Sutikno; Marniza Marniza; Meri Fitri Yanti (Jurnal Teknologi & Industri Hasil Pertanian, 2015)
The objective of this research was to obtain the best treatment on empty palm fruit bunch (EPFB) to produce reduced sugar.  Two treatments were applied on the EPFB.   The first treatment was EPFB submersion into 0 M and 0.50 M NaOH solution at a temperature of121oC for 15minutes and the second treatment was sulfuricacid concentration.   After drying and grinding, 1.5 g EPFB was put into 100 mL Erlemeyer flash, added with 30 mL 1.0 M NaOH solution, and then heated at a temperature of 121oC for 15 minutes.  The solution was filtered and the residue was hydrolyzed with H2SO4 solution.  The residue as well as 1.5 g EPFB without treating with NaOH was hydrolyzed with 15 mL H2SO4 at concentrations of 0, 0.05, 0.10, 0.20, and 0.30 M at a temperature of 121oC for 15 minutes. After filtering the solution, the EPFB were analyzed to determine their reduced sugar contents.   Reduced sugar contents of the EPFB ranged from 0.07 to 8.36 mg/100 mL.  The best treatment in this research was submersion EPFB samples in 1.0 M NaOH solution and then hydrolysis with 0.05 M H2SO4 at a temperature of 121oC for 15 minutes.  The treatment resulted in 8.36 mg reduced sugar /100mL.  Keywords: Empty Palm Fruit Bunches, reduced sugar, lignocelluloses, sulfuric acid, NaOH